Improving the Quality of Student Learning at SMP Negeri 1 Pammana, Wajo Regency in Pai Subjects through the Application of Cooperative Learning Type Card Sort - Nurjannah Nurjannah; Muhammad Arifai; Mustaking Mustaking; Najmiah Najmiah; Hamdi Hamdi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
The school level's learning conditions in general and especially at SMP Negeri 1 Pammana are still coloured by the emphasis on the aspect of knowledge, and there is still little that refers to the involvement of students in the learning process itself. As a result, students get the learning result score is still below the average of 60.00. This research is a Classroom Action Research, which includes four stages of implementation, namely: planning, action/implementation, observation/evaluation, and reflection. This study consisted of two variables, namely: first, the free variable type card sort cooperative learning. Second, the dependent variable is the quality of knowledge of grade VIII students of SMP Negeri 1 Pammana. The results showed that the learning quality of Islamic religious education for VIII B grade students at SMP Negeri I Pammana in the 2007/2008 academic year had increased through the application of card sort type cooperative learning. Namely, the increase in student activity in the learning process, indicated by student learning outcomes with an average value of 60.70 in the first cycle, increased to 70.70 in the second cycle.